TREND IN BIOLOGY EDUCATION RESEARCH FROM 2012 TO 2017: A CONTENT ANALYSIS OF PAPERS IN SELECTED JOURNALS FROM INDONESIA - M. Haviz; M Ridho (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
TREN PENELITIAN PENDIDIKAN BIOLOGI 2012-2017: ANALISIS KONTEN PAPER DI JURNAL TERSELEKSI DARI INDEKS PUBLIKASI INDONESIA AbstrakArtikel ini telah menjelaskan kajian tentang tren penelitian di bidang penelitian pendidikan biologi di Indonesia sepanjang tahun 2012-2017. Studi ini telah menganalisis artikel-artikel yang telah dipublikasikan di jurnal ilmiah yang telah diindeks di Indonesia Publication Index. Pada bagian pendahuluan penelitian, kami telah menemukan hanya empat jurnal yang memiliki skop secara spesifik di bidang pembelajaran biologi. Keempat jurnal tersebut adalah Journal of Biology Education, Bioedu, Bioedukasi dan Didaktika Biologi. Dalam keempat jurnal ini kami juga telah menemukan 547 artikel yang telah dipublikasikan sejak tahun 2012-2017. Semua artikel ini telah diunduh dan dilakukan analisis konten. Analisis konten dilakukan mengacu kepada tujuh aspek yaitu topik biologi, subjek penelitian, metode/desain penelitian, elemen penelitian, alat pengumpul data, jenis dan ukuran sampel dan teknik analisis data. Data yang telah diperoleh, telah dianalisis dengan statistik deskriptif dan telah ditampilkan dalam bentuk tabel dan grafik. Kesimpulan penelitian ini adalah tren penelitian di bidang penelitian pendidikan biologi di Indonesia sepanjang tahun 2012-2017 dibedakan menjadi tujuh kategori yaitu topik biologi adalah bentuk dan fungsi hewan, subjek penelitian adalah pengajaran dan pembelajaran, metode/desain penelitian adalah eksperimen, elemen penelitian adalah kognitif, alat pengumpul data adalah tes prestasi belajar, jenis sampel adalah siswa-siswa sekolah menengah atas dan ukuran sampel adalah 31-100 dan teknik analisis data adalah teknik kuantitatif..AbstractThis article was to describe research trends in Biology Education Research (BER) in Indonesia across year 2012-2017. This study was conducted by descriptive quantitative, with a content analysis the article that has been published in scientific journals that indexed in the Indonesia publication index. The content analysis were refer to sevent subjects were biology topics, teaching and learning, research design/methods, research element, data collection tools, samples and sample sizes and technique of the data analysis. The data obtained were analyzed with descriptive statistics and displayed in tables and graphs. We founded that only four journals have been scope specifically in the biology learning. The four journals were Journal of Biology Education, Bioedu, Bioedukasi and Didaktika Biologi. In theses journals, we also found 547 articles published from 2012-2017. All of these articles were downloaded and all of theses articles were subjected to content analysis. The result of the study showed that research trends BER in Indonesia across the year 2012-2017 were devide on seven categorizes such as; biology topics was animal form and function, teaching and learning was subject matter, research design/methods was quantitative experimental design, research element was cognitive, data collection tools was achievement test, samples was the students at Senior High School (SMA) and the size of samples was between 31-100 and technique of the data analysis was quantitative method. The implication of this study has implicated that to be an information for the researcher being conduct their researchs. The result of this study also will be contributed for the teachers and educator in teaching and learning of research of methodology in biology education.